Conservation through education - Light, Marilyn H. S. (Universidad de Costa Rica, 2016)
The way to conservation is through education. People of all ages everywhere are learning how to make wise use of natural resources to ultimately ben- efit and sustain future generations but clear goals, objectives and analogies are needed to reinforce the message. Conservation education initiatives can be compared to production of a food crop. A crop plant must first be selected to suit the growing environment then the fields prepared for planting. After planting, the growing plants must be cared for. Only after a successful harvest can the profit be realized.